Faint White Dwarf Flux Standards: Data and Models - Ralph C. Bohlin; Susana Deustua; Gautham Narayan; Abhijit Saha; Annalisa Calamida; Karl D. Gordon; Jay B. Holberg; Ivan Hubeny; Thomas Matheson; Armin Rest (The Astronomical Journal)
Fainter standard stars are essential for the calibration of larger telescopes. This work adds to the calibration spectra (CALSPEC) database of 19 faint white dwarfs (WDs) with all-sky coverage and V magnitudes between 16.5 and 18.7. Included for these stars is a new ultraviolet (UV) Hubble Space Telescope (HST) Space Telescope Imaging Spectrograph between 1150 and 3000 Å with a resolution of ∼500. Pure hydrogen WD models are fit to these UV spectra and to six-band HST/Wide Field Camera 3 photometry at 0.28–1.6 μ m to construct predicted model spectral energy distributions covering wavelengths from 900 Å to the James Webb Space Telescope limit of 30 μ m using well-established CALSPEC procedures for producing flux standards with the goal of 1% accuracy.